Pengaruh Penerapan Corporate Sosial Responsibility (Csr) Internal Pt. Pandji Waringin, Tbk Terhadap Motivasi Kerja Karyawan - Rindiyani, Nopi; Deni Kencana, Agus; Nurjamal, Nurjamal (GEMA EKONOMI, 2023)
The purpose of this study was to determine the effect of the implementation of Internal Corporate Social Responsibility (the dimensions of Human Resource Management and the dimensions of Occupational Health and Safety) at PT. Pandji Waringin, Tbk on employee motivation. A quantitative approach is used in this research strategy, namely research that emphasizes hypothesis testing. This type of research uses explanatory research. Questionnaires were given to 102 participants who were employees at PT. Pandji Waringin, Tbk in this study was used to collect data. The results of the study stated that the implementation of the dimensions of Human Resource Management and Occupational Health and Safety had a moderate effect but brought a positive direction to employee motivation. So, the magnitude of the relationship together with the independent variables (Human Resource Management and Occupational Health and Safety) has a moderate relationship